The SmartAG Partner: CCAFS East Africa Quarterly Newsletter, April - June 2017 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
Dear readers, We are pleased to share with you our SmartAg Partner newsletter, highlighting policy engagement and ongoing research in the second quarter of 2017. In May, we hosted a seminar that explored the state of climate adaptation and mitigation efforts in African agriculture. The seminar created an opportunity for about 65 stakeholders and scientists from CGIAR centers to share knowledge, learn from each other and build synergies on climate change adaptation and mitigation in East Africa. We took this opportunity to launch our booklet that outlines some of the emerging success stories of climate-smart agriculture technologies and practices that are positively changing the lives of smallholder farmers across East Africa. CCAFS scientists authored and guest edited the recently published Special Issue on Climate-Smart Agriculture of the Agriculture for Development journal. The journal features an article about managing climate risks through small ruminants in the Nyando Climate-Smart Villages and our policy engagement processes that focus on integrating climate change and agriculture policies in East Africa. Additionally, three of our research papers were published recently in a book titled ’Climate Change Adaptation in Africa: Fostering Resilience and Capacity to Adapt’. The book is an output of a symposium held last year where researchers from CCAFS East Africa presented emerging results from the Nyando Climate-Smart Villages. In the latest CCAFS Annual Report, stories highlight working with scientists, farmers, governments and the private sector to expand knowledge and scale up solutions. The report features initiatives from East Africa, such as projects on climate risk management, and partnerships aiming to close the gender gap in African agriculture, among others. We have also published a number of project stories on the CCAFS blog, for instance, about a recent training of trainers workshop in Rwanda, where stakeholders learned about how to encourage farmers to take decisions by providing them with weather and climate information. Dr. Dawit Solomon